Kinerja Koperasi Karyawan Widhya Guna Artha Denpasar Provinsi Bali: Pendekatan Balanced Scorecard - I Wayan Yudi Suwanda; Ketut Suamba; Ni Wayan Sri Astiti (JURNAL MANAJEMEN AGRIBISNIS, 2016)
Until now the company's or cooperative’s performance appraisal much more from the financial side.For a more comprehensive measurement and assessment, carried out a balanced scorecard approach. This study aimed of performance Employees Cooperative Widhya Artha Guna evaluated from four perspectives Balanced Scorecard ie, financial, customer, internal business processes, and learning and growth. The period of 2011-2014 have been chosen according to actuality and completeness of the data.Population and sample that are committee, members and customers of the cooperative.Type of data are quantitative and qualitative data. Primary and secondary data sources.Collecting data using the method of documentation, questionnaire, interview and observation.Data analysis using quantitative and qualitative descriptive method. Results of the study are: (1) Employees Cooperative Performance Widhya Artha Guna Denpasar in terms of the financial perspective by using several criteria: liquidity ratio, profitability, solvency, leverage ratio, and the ratio of activity from 2011-2014 showed an excellent performance from aspects of underwriting and health financial but worth considerably less until enough of the performance aspects of economic activities of businesses in terms of maximizing the utilization of assets to earn extra profit. From the aspect ratio for historical, cooperative performance can be said to be stable. (2) from the customer perspective on aspects of customer satisfaction showed a dominant enough because customers are skeptical of the quality of service cooperatives, but on aspects of customer acquisition, showed a good performance because it is able to grow or acquire customers in over 10% every year. (3) of the internal business process perspective on aspects of transaction processing credit and aspects of transaction processing savings deposits indicates that the business process has been running efficiently (4) of the learning and growth perspective on aspects of employee productivity is good, which is demonstrated by employee productivity during the last four years (2011-2014) continues to increase. While aspects of employee satisfaction is approached from the five dimensions of work mentally, dimensions rewards, the dimensions of working conditions, dimensions coworkers, and dimensional suitability of personality to the job, shows that the overall dimensions of the employees said they were satisfied except in dimensions reward employees feel mediocre. Results can be submitted suggestions (1) a need to improve business activities utilize the excess assets to increase profit. (2) It is necessary to evaluate the services to the customers. (3) It should be evaluated compensation granted to employees (4) It should be further research by other researchers to add a new perspective is the confidence (trust).